Peningkatan Hasil Belajar Bilangan Bulat Melalui Pengguanaan Media Kancing Warna Pada Siswa Kelas V Semester 1 SDN 1 Patalan Blora Tahun Ajaran 2015/2016 - Slamet, Slamet, Drs. Djumadi, M.Kes (2015)
The research problems in this class action, namely the low achievements of student learning in the Integers, then learning to improve learning achievements is done by involving students directly in emotional adn social, among teachers with students or students wint students interaction must occur in order to find a concept and understanding a concept jointly - the same. The purpose of this research is to enliven the translated media in learning color studs Integres and analyze the impact of the use of the color buttons in the media against the learning achievements of students. This research is a research class action because it was implemented to improve teacher performance results in managing learning. Step -step taken in this research as much as to cycles. Each cycle consists of four stages, namely planing, imlementation,observasion, adn reflection. This research was carried out on SDN 1 Patalan Blora with the subject of research is the grade V semester lesson I in 2015 - 2016. The results of this research it can be concluded that Media buttons collor can improve learning outcomes the integers grade V SDN 1 Patalan Blora. The avarage value of the class in prasiklus is succesfully and the rate of 47,1 students 25%. After the cycle I, held averages grade rose to 57,3 successfully with a level 50%. While the median cycle 74,6 with successfully level of 88%.